Making things happen: How employees’ paradox mindset influences innovative performance - Liu, Yanjun; Zhang, Hui (Frontiers in Psychology, 2022)
Individual innovation involves many contradicted behavioral options such as creative vs. habitual actions and explorative vs. exploitative activities. However, the agentic nature of innovative behaviors has been widely ignored, and we know less about what factors lead individuals to approach and balance the contradictions caused by competing demands and intentionally engage in innovative behaviors. Integrating social cognitive theory and innovation paradox, we propose a chain-mediating model to explain how employees with a paradox mindset realize the creative benefits through their innovative endeavors, considering role breadth self-efficacy (RBSE) and individual ambidexterity as two mediators. Using data collected from 480 employees paired with 100 supervisors at 3-time points, the results show that RBSE and individual ambidexterity play a mediating role, respectively, even though they sequentially play a chain-mediating role between employees’ paradox mindset and innovative performance. Individuals who hold a paradox mindset are more likely to perceive high capability beliefs in successfully undertaking expanded roles, promoting behavioral tendencies to switch between exploration and exploitation, and in turn encouraging employees to undertake more innovative behaviors. Finally, we discuss the theoretical and practical implications for promoting employees’ innovative performance from an agentic perspective. Employees with a paradox mindset can make creative things happen by managing the tensions between exploration and exploitation proactively. Thus, organizations may try to enhance employees’ proactive motivation states and behavioral capability to encourage individual innovation.